Optimasi Metode Ekstraksi Mikroplastik Polivinil Klorida (PVC) Dengan Wet Peroxide Oxidation (WPO) - Deliani, Nur Farida; Dewata, Indang (Departemen Kimia FMIPA UNP, 2024)
The increase in plastic production causes an increase in plastic waste in the environment both on land and in waters. Over time, plastic waste will degrade into microplastics in waters. Microplastics in waters are contaminated with organic impurities which can interfere with the identification of microplastics. The method for extracting plastic particles from organic impurities is using wet peroxide oxidation. However, these methods have not been systematically tested and standardized. This research aims to determine the optimum conditions for the extraction method with the addition of wet peroxide oxidation for the identification of PVC microplastics. In this research, a 30% hydrogen peroxide solution was used as an oxidizer and a Fe2+ catalyst as the main ingredient to produce OH radicals which function to oxidize organic impurities and the samples used were PVC microplastics made from grinding PVC plumbing pipes. Determination of optimum conditions was carried out at varying oven temperatures of 70oC, 80 oC, 90 oC, 100oC, dan 110oC, varying concentrations of 0,025 M; 0,05M; 0,075M; 0,1M dan 0,125M and temperature variations at heating 30oC, 45oC, 60oC, 75oC, dan 90oC, as well as testing the optimum extraction method on water samples with water volumes ranging (200, 400, 600, 800, and 1000) mL. The research results showed that the optimum conditions were an oven temperature of 90oC, a Fe catalyst concentration of 0.075M, and a heating temperature of 75oC in the PVC microplastic extraction process resulting in a PVC microplastic mass of 0.3403 grams. Characterization of PVC microplastics was carried out using Primostar 1, FTIR and XRF microscope instruments. Tests using a microscope showed that the form of PVC microplastic was identified, namely fragment form. In the FTIR test, CH2, C-Cl, C-C peaks were obtained which indicated that the polymer was a type of PVC, apart from that there were N-H bend dan N-H stretching peaks which indicated the material. The organic impurities are in the form of amine, and in XRF testing the additive elements that make up PVC microplastics are obtained, namely Si, P, Ca, V, Cu, Br, Sr.